The effect of off-season training load on lactate threshold, strength, and rowing performance in collegiate division 1 rowers - Kowalczyk, K.; Hudak, J.; Taber, C. (2020 Academic Festival, 2020)
Collegiate rowers require efficient aerobic and anaerobic power to perform at an elevated level. The Pioneer Performance Center at Sacred Heart University in conjunction with the Sacred Heart Crew team developed a testing battery to assess the team`s aerobic and anaerobic proficiency. Twenty-one female rowers completed testing in the Fall and Spring semesters (Average Age: 19.1 years; Height: 167.05 cm; Weight: 69.33 kg). Data was collected over a two-week period. The three assessments included grip strength, isometric leg strength, and lactate threshold. Data analysis and descriptive statistics were produced in Microsoft Excel. Statistically significant improvement was found in right hand grip strength. Averages for all assessments increased from the Fall to Spring semester. The data collected provides a start for a database of norms to be created by the Pioneer Performance Center for the crew team. Future work should continue to assess the crew team in the Fall and Spring semesters and branch out to local rowing clubs.